The Effect of Receivables Financing and Profit Sharing Financing on Profit at Bank Sumut Syariah - Ruswin, Muhammad; Arwin, Arwin (Universitas Ibn Khaldun, 2025)
This study was conducted to see the effect of receivables financing, profit sharing financing and PROFIT on Bank Sumut Syariah for the period 2017-2023. This study aims to determine how much influence receivables financing has on PROFIT, the effect of profit sharing financing on PROFIT and the effect of receivables financing and profit sharing financing together on PROFIT at Bank Sumut Syariah. This study uses a quantitative approach with secondary data. The population in this study is the quarterly financial report of Bank Sumut Syariah which has been published through its official website. The sample in this study is the financial position report and profit and loss report from 2017-2023. The sampling technique in this study uses the Purposive Sampling method, where Purposive Sampling is a deliberate sampling technique. Researchers determine the sample to be taken themselves. The dependent variable (Y) in this study is PROFIT, the independent variable (X) is receivables financing (X1), profit sharing financing (X2). The tool in this study uses SPSS version 20. Based on the results of the SPSS calculation, the results of the study show that receivables financing has a positive and significant effect on PROFIT at Bank Sumut Sayriah, this is evidenced by the t-count value < from t-table, namely t-count 3,860 < t-table 1.694, with a significance value of 0.01 < 0.05. Profit sharing financing does not have a significant effect on PROFIT at Bank Sumut Sayriah, this is evidenced by the t-count value X2 = 0.178 and t-table 1.694. So that t-count> t-table (0.178> 1.694), with a significance value of 0.086> 0.05. Then the results of the study showed that receivables financing and profit sharing financing simultaneously or together affect PROFIT at Bank Sumut Sayriah, this is evidenced by the calculated F value of 8.820> F table 3.295 (8.820> 3.295), with a significance value of 0.001 <0.05.